Structural Changes and their Econometric Modeling - Kreinovich, Vladik; Sriboonchitta, Songsak (Studies in Computational Intelligence, 2019)
This book focuses on structural changes and economic modeling. It presents papers describing how to model structural changes, as well as those introducing improvements to the existing before-structural-changes models, making it easier to later on combine these models with techniques describing structural changes. The book also includes related theoretical developments and practical applications of the resulting techniques to economic problems. Most traditional mathematical models of economic processes describe how the corresponding quantities change with time. However, in addition to such relatively smooth numerical changes, economical phenomena often undergo more drastic structural change. Describing such structural changes is not easy, but it is vital if we want to have a more adequate description of economic phenomena - and thus, more accurate and more reliable predictions and a better understanding on how best to influence the economic situation.